VIGS en die Suid-Afrikaanse ekonomiese en bestuurswêreld - Enkele perspektiewe - Schutte, P. C. (Koers, 1990)
There is no doubt anymore that AIDS as a disease has the potential to become a very serious issue in the South African social, political, demographic and economic environment. AIDS will have macro-economic as well as micro-business implications. At macro-level (without the influence of AIDS) decision-makers already anticipate and plan for a • shortage in housing for blacks; • shortage in employment opportunities; • high level of unemployment; • uncontrollable urbanisation; and a • lack of educational infrastructure. Burning issues for decision-makers and managers will be • who will be the worker tomorrow? • who will be the manager? • will there be sufficient manpower resources? • what would a training strate& took like ? • in what ways will production and productivity be managed? • in what ways will sound labour relations be created and maintained? Although a great many decision-makers and managers still have a sceptical view and perception regarding AIDS, it is certain that it will affect the entire spectrum of life. Managers should proactively plan for the implications of AIDS on business, and if projections do not realise as darkly, it could be seen and accepted as a "bonus"